2022
DOI: 10.1002/fsn3.2919
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extraction methods on the efficiency of sumac (Rhus coriaria L.) fruit extract in soybean oil quality during accelerated conditions

Abstract: Herbal extracts containing natural bioactive substances with numerous beneficial effects have been recently noticed as appropriate alternatives for synthetic food preservatives. In this study, we aimed to optimize the effects of different sumac (Rhus coriaria) fruit extracts (SFE) on oxidative stability of soybean oil under accelerated conditions compared to a synthetic antioxidant. Hydro‐ethanolic extracts (70%) of sumac fruits were prepared by three methods of immersion (I‐SFE), ultrasound (U‐SFE), and micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In other words, the generation of off‐flavor and off‐odor compounds (e.g., peroxides, aldehydes, polar compounds, and conjugated dienes) was significantly ( p ≤ .05) decreased by PPE compared to the negative control group, leading to the high quality of the studied samples until the end of the accelerated storage period. Rahmati et al ( 2022 ) reported that sumac fruit extract‐containing groups significantly ( p ≤ .05) earned the highest scores of the sensory characteristics of the fried potatoes in the soybean oil under accelerated conditions compared to the control group and showed the same performance as the BHT‐containing treatment. Another study reported that the sunflower oil‐containing Coriandrum sativum essential oil (1200 ppm) showed desirable aroma and flavor over the accelerated storage period.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In other words, the generation of off‐flavor and off‐odor compounds (e.g., peroxides, aldehydes, polar compounds, and conjugated dienes) was significantly ( p ≤ .05) decreased by PPE compared to the negative control group, leading to the high quality of the studied samples until the end of the accelerated storage period. Rahmati et al ( 2022 ) reported that sumac fruit extract‐containing groups significantly ( p ≤ .05) earned the highest scores of the sensory characteristics of the fried potatoes in the soybean oil under accelerated conditions compared to the control group and showed the same performance as the BHT‐containing treatment. Another study reported that the sunflower oil‐containing Coriandrum sativum essential oil (1200 ppm) showed desirable aroma and flavor over the accelerated storage period.…”
Section: Resultsmentioning
confidence: 98%
“…During poor processing and storage conditions of the oils, such as high relative humidity, heating, and tissue damage, the intensity of this reaction significantly increases. Since the released FFAs are very sensitive to the oxidation reaction, following the oil hydrolysis, oxidation is intensified (Rahmati et al, 2022 ). The oxidation reaction of edible oils is the most common phenomenon, which is accelerated by increasing their storage time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have proposed simple methods such as peroxide index and acid number to determine the durability based on sensory tests (Huang, Hou, et al, 2022 ; Li, Wang, & Ye, 2022 ; Rahmati et al, 2022 ). Figure 1 shows the sensory evaluation of butter samples of the control group and samples treated with different concentrations of fucoidan on different days.…”
Section: Resultsmentioning
confidence: 99%